Developing a Participatory, Integrative, and Collaborative Competency-Based Training Model (PIKOLAK) through Blended Learning to Enhance the Teachers’ Professional Competence - Benyamin Nababan; Sahat Siagian; Abdul Hamid; Holmes Rajagukguk (Association of Language Teachers in Southeast Asia (ALTSA), 2025)
This study employed a Research and Development (R&D) methodology to design, develop, and evaluate the Participatory, Integrative, and Collaborative Competency-Based Training Model (PIKOLAK), utilizing a blended learning approach to enhance the professional competence of teachers in Humbang Hasundutan Regency. The development process followed an iterative sequence of stages, including a comprehensive needs analysis, systematic model design, expert validation, and rigorous field testing. The blended learning framework integrated face-to-face sessions with online components, allowing for greater flexibility and accessibility while maintaining instructional quality. The implementation of the PIKOLAK model resulted in a marked improvement in teachers' professional competencies. Quantitative analysis revealed a statistically significant increase in mean test scores, rising from 65.2 on the pre-test to 83.7 on the post-test (p < 0.01). These findings suggest that the model effectively addressed gaps in teachers' knowledge and skills. Qualitative feedback from participating teachers further supported these outcomes, indicating increased engagement, stronger collaborative practices, and enhanced application of pedagogical competencies in real classroom contexts. The participatory and integrative learning strategies embedded in the model were particularly appreciated, as they fostered a sense of ownership and relevance among learners. Overall, the results affirm that the PIKOLAK model is a valid, reliable, and effective framework for advancing teacher professional development. Its blended format offers a scalable and adaptable solution that accommodates diverse learning needs while promoting sustainable, practice-based improvements in educational quality. Consequently, the model holds significant potential for broader implementation across similar educational contexts.